2020
DOI: 10.14814/phy2.14345
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dual‐specificity protein phosphatase 5 on mechanical properties of rat cerebral and renal arterioles

Abstract: We recently reported that KO of Dual-specificity protein phosphatase 5 (Dusp5) enhances myogenic reactivity and blood flow autoregulation in the cerebral and renal circulations in association with increased levels of pPKC and pERK1/2 in the cerebral and renal arteries and arterioles. In the kidney, hypertension-related renal damage was significantly attenuated in Dusp5 KO rats. Elevations in pPKC and pERK1/2 promote calcium influx in VSMC and facilitate vasoconstriction.However, whether DUSP5 plays a role in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
4
33
0
1
Order By: Relevance
“…This group discovered impaired endothelial-dependent vasodilation due to loss of TRPV4 in the endothelium of cerebrovasculature in chronic SCI, together with increased vascular stiffness, contributes to cerebral hypoperfusion and cognitive deficits in chronic SCI. Cerebral parenchymal arterioles are a bottleneck of the cerebral circulation and play a major role in regulating CBF [ 9 ]. Remodeling and endothelial dysfunction of cerebral parenchymal arterioles could cause cerebral ischemic injury leading to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This group discovered impaired endothelial-dependent vasodilation due to loss of TRPV4 in the endothelium of cerebrovasculature in chronic SCI, together with increased vascular stiffness, contributes to cerebral hypoperfusion and cognitive deficits in chronic SCI. Cerebral parenchymal arterioles are a bottleneck of the cerebral circulation and play a major role in regulating CBF [ 9 ]. Remodeling and endothelial dysfunction of cerebral parenchymal arterioles could cause cerebral ischemic injury leading to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cerebral VSMCs were isolated from the MCA of 3-week old male SD rats, as described earlier [54][55][56][57]. Briefly, the MCAs that were dissected from the brain were placed in ice-cold Tyrode's solution, containing contained 145 mM NaCl, 6 mM KCl, 1 mM MgCl2.6H2O, 50 uM CaCl2.2H2O, 10 mM HEPES sodium salt, 4.2 mM NaHCO3, 10 mM Glucose; pH 7.4.…”
Section: Cell Culturementioning
confidence: 99%
“…After incubation, the stressed matrix was detached from the wall of the plate using a sterile needle to initiate the cell contraction. Changes in the collagen gel area were measured using the equation: contraction (%) = [(Areawell -Areagel) / Areawell] X 100% and quantified with Image J software as we previously described [54][55][56][57].…”
Section: Cell Contraction Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of genes in the 2.4‐Mbp region of chromosome 1 revealed 15 known and predicted genes in the region, of which three genes (γ‐adducin ( Add3 ), dual‐specificity phosphatase 5 ( Dusp5 ), and X‐prolyl aminopeptidase 1 ( Xpnpep1 )) exhibit sequence variants in the coding regions (Burke et al., 2013). DUSP5 is a member of the threonine/tyrosine phosphatase family with the ability to specifically dephosphorylate the key molecules that regulate intracellular signal transduction, including extracellular signal‐related kinase and protein kinase C (PKC) (Kucharska et al., 2009; Owens & Keyse, 2007; Zhang et al., 2020). A study revealed that knockout (KO) of Dusp5 enhanced the myogenic response of the middle cerebral artery and autoregulation of cerebral blood flow in FHH rats (Fan et al., 2014).…”
Section: Genes Involved In the Regulation Of Renal Hemodynamicsmentioning
confidence: 99%